ANALISIS DIGRAPH DARI TABEL CAYLEY GRUP DIHEDRAL - Abidin, Wahyuni (Fakultas Sains dan Teknologi UIN ALauddin, 2013)
Graph theory is a part of mathematics, in which there are explanations of digraphs. This research, purposed to show a table based on Cayley digraphs depiction dihedral group. A digraph can be described from a group, one of which is the operation of the Cayley table of the dihedral group. Dihedral group is the group of the set of symmetries n-terms of regular, denoted D2n, for each positive integer n, n ï³ 3. This, the dihedral group will be divided into two subsets, namely:1. x = 1, r, ,... or known with subsets rotation;2. v = s, sr, ,... or known with subsets reflection.Based on the analysis of this research showed that, to obtain a connected digraphs, the depiction of these digraphs, dihedral group can be formed on the element generator, generator (r, s), and the generator (s, sr) to form a composite image with elements digraphs elements x and y. on the operation of the Cayley table dihedral group, which contained depictions digrap shekel same cannot be combined. From the results of the operation of the rotation and reflection on the dihedral group D6 Cayley table which is a group of abstract forms, latin squares, which can be described by a digraph elements of the generator it.Keyword: Eulerian digraph, Hamilton digraph, Cayley Table, Dihedral group, Reflection, Rotation.